Descripción de primeros registros micomórficos para el Ecuador - Gamboa, Paul (2017)
The Archaeological Museum Antonio Santiana Central University of Ecuador, Quito; has a collection of archaeological importance to the study of social behavior of the ancestors of this region, becoming the strategic site to locate two possible micomorphical estructures. One of them in pictorial design decorating a concave bowl-like characters similar by Geastrum sp. belonging to the Cuasmal culture. The second features is a ceremonial cup, similar to agaricales macrofungi by Man- 258 teña culture. These pieces represent the possible traces that explain use of macrofungi, seen as beneficial and sacred rituals used for events. They also reveal the importance of studying, by bioarchaeology, mycophylous customs shared with other communities in America, with whom there was a heavy exchange of products and knowledge that are expressed to this day, to a lesser degree by the advent of modern life the mixture of cultures.